ChatGPT in didactical tetrahedron, does it make an exception? A case study in mathematics teaching and learning - Dasari, Dadan; Hendriyanto, Agus; Sahara, Sani; Suryadi, Didi; Muhaimin, Lukman Hakim; Chao, Theodore; Fitriana, Laila (Frontiers in Education, 2024)
The Didactical Tetrahedron model proposes a framework for integrating technology into the previous didactical triangle. This study addresses this issue through examining the role of ChatGPT in educational settings. This quantitative and qualitative study reveals differences among three groups. We observed that students relying solely on ChatGPT for learning resulted in lower performance compared to those receiving instruction from teachers, either alone or supported by ChatGPT. The findings highlight the potential of ChatGPT in enhancing mathematical understanding, yet also underscore the indispensable role of instructors. While students generally perceive ChatGPT as a beneficial tool for learning mathematical concepts, there are concerns regarding over-reliance and the ethical implications of its use. The integration of ChatGPT into educational frameworks remains questionable within a didactic context, particularly due to its limitations in fostering deep information comprehension, stimulating critical thinking, and providing human-like guidance. The study advocates for a balanced approach, suggesting that ChatGPT can augment the learning process effectively when used in conjunction with guidance. Thus, positioning technology as an independent focal point in transforming the didactic triangle into a didactical tetrahedron is not appropriate, even when represented by ChatGPT.